COMPARATIVE ANALYSIS OF PRECAST CONCRETE FLOOR SLAB WITH CAST IN SITU AND STRUCTURE STABILITY OF GKB UPN "VETERAN" EAST JAVA - Alma Christine Puspasari Rumaseb; Made Dharma Astawa; Sumaidi (Journal of Civil Engineering Science and Technology (CI-TECH), 2020)
Gedung Kuliah Bersama was modified into ten floors, constructed using precast pretension slabs, namely hollow core slabs on the second to five floors and cast in situ slabs, namely steel deck on floors six to ten. Gedung Kuliah Bersama is located at the UPN “Veteran” East Java in the city of Surabaya. Geologically and tectonically, Surabaya City is in an active fault zone, so that the tectonic activity that occurs can cause damage to building structures and construction materials. Pushover analysis is an analysis that can be used to determine the pattern of structural collapse when an earthquake occurs. Based on the results of the analysis, precast pretension slabs (hollow core slabs) with segments of 1500 mm × 7000 mm × 150 mm with PC Wire reinforcement ϕ7-121 mm and cast in situ (steel deck) slabs with a thickness of 120 mm with wiremesh reinforcement M8-150 mm. The difference in the bending strength of the two types of slabs is 38.73%. The results of the pushover analysis show that the structural performance at the Damage Control (DO) level shows that the building is able to withstand the earthquake that occurs and the risk of casualties is very small.